PENGARUH CURAH HUJAN, HARGA JUAL DAN JUMLAH PRODUKSI KARET TERHADAP PENDAPATAN PETANI KARET DI KABUPATEN DHARMASRAYA - Agustin, Meli; Nefilinda, Nefilinda; Putri, Rozana Eka (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research aims to determine the effect of rainfall, selling price and amount of rubber production on the income of rubber farmers in Dharmasraya RegencyThis type of research is descriptive correlational. The population in this study were all rubber farmers in Dharmasraya Regency, totaling 13,969 rubber farmers. The research samples were taken based on the simple randam sampling technique, which used the slovin technique with a proportion of 10%, so that the sample consisted of 99 rubber farmers.The research results found that: 1) there is a significant influence of rainfall on the income of rubber farmers in Dharmasraya Regency because tcount > ttable (1.316> 0.196), the magnitude of the influence is very strong with (r = 0.834) and the contribution is quite large at 47.2% , (2) there is a significant influence of the selling price of rubber on the income of rubber farmers in Dharmasraya Regency because tcount > ttable (0.864 > 0.196). The influence of the selling price of rubber is very strong with (r = 0.974) and a large contribution (71.6%), (3) there is a significant influence of the amount of rubber production on the income of rubber farmers in Dharmasraya district because tcount> ttable (8.588> 0.196), The influence of the amount of rubber production is strong (r = 0.657) and the contribution is quite large (43.2%), (4) there is a significant influence of rainfall, rubber selling price, and the amount of rubber production together on the income of rubber farmers in the Regency. Dharmasraya because Fcount > Ftable (7.122 > 4.07), the magnitude of the influence of the four variables on the income of rubber farmers in Dharmasraya district is very strong (r = 0.916), while the magnitude of the contribution is quite large (44.2%).Keywords: rainfall, selling price, rubber production, income of rubber farmers